Evolução morfotectônica do maciço estrutural pereiro, Província Borborema - Gurgel, Silvana Praxedes de Paiva (2012)
The Northeast relief was described by the Pediplanation Model. This action discards the theoretical basis of post-Cretaceous tectonic evolution of the landscape. Through this model the Massif Pereiro - MP, Borborema Province, was established as part of the Tablelands Area Residual Sertanejos. The present work aims to establish the post- Cretaceous morphotectonic evolution of the MP by geomorphological and geological mapping using Geographic Information System, Remote Sensing and dating of sediments by Single Aliquot Regenerative-dose (SAR). The MP is contained in the core semi-arid, annual precipitation of 600-800 mm / year. The MP is NE-SW, is limited by Shear Zone Jaguaribe (ZCJ) and Portalegre Shear Zone (ZCPa), the same attitude, and crossed by several other shear zones. These shear zones show evidence of brittle Cenozoic reactivation, mostly as normal faults and shallow crustal level. The Quaternary sedimentation around the MP focuses on fault escarpments in a general pattern cascade, where ages decrease from the summits of the steep foothills. The ages of 51 sediment samples indicate a correlation with global climate following pulses: Last Interestadial-UI, the Last Glacial Maximum - LGM and the transition Pleistocene / Holocene, while the latter focus on 18 of 51 samples dated. This study also finds evidence of a new quaternary basin, here called Merejo Basin. Through these results it is concluded that no evidence of post-Cretaceous tectonic evolution of morphological MP, as their retreat along the fault scarps, invariably following the trend of the shear zones. The erosion of cliffs in large time scale is controlled by weakness zones generated by faults on the other hand the erosion of cliffs in short time, with the formation of deposits and colluvial horizons pedogenizados, has climate control. It was also found that in the study area there is a preponderance of past and current tectonic erosion processes on the morphological evolution